Alkaline flocculation of Phaeodactylum tricornutum induced by brucite and calcite. (November 2015) - Vandamme, Dries; Pohl, Philip I.; Beuckels, Annelies; Foubert, Imogen; Brady, Patrick V.; Hewson, John C.; Muylaert, Koenraad
Highlights: Both brucite and calcite are involved in alkaline flocculation in marine conditions. Flocculation efficiency reached 90% at pH 10.5 consistent with precipitation models. Mg precipitated as brucite caused flocculation dominantly by charge neutralization. Ca precipitated as calcite caused flocculation dominantly by sweeping flocculation. Abstract: Alkaline flocculation holds great potential as a low-cost harvesting method for marine microalgae biomass production. Alkaline flocculation is induced by an increase in pH and is related to precipitation of calcium and magnesium salts. In this study, we used the diatom Phaeodactylum tricornutum as model organism to study alkaline flocculation of marine microalgae cultured in seawater medium. Flocculation started when pH was increased to 10 and flocculation efficiency reached 90% when pH was 10.5, which was consistent with precipitation modeling for brucite or Mg(OH)2 . Compared to freshwater species, more magnesium is needed to achieve flocculation (>7.5 mM). Zeta potential measurements suggest that brucite precipitation caused flocculation by charge neutralization. When calcium concentration was 12.5 mM, flocculation was also observed at a pH of 10. Zeta potential remained negative up to pH 11.5, suggesting that precipitated calcite caused flocculation by a sweeping coagulation mechanism.